Investigating Students' Development of Learning Integer Concept and Integer Addition - Shanty, Nenden Octavarulia (Journal on Mathematics Education, 2016)
This research aimed at investigating students' development of learning integer concept and integer addition. The investigation was based on analyzing students' works in solving the given mathematical problems in each instructional activity designed based on Realistic Mathematics Education (RME) levels. Design research was chosen to achieve and to contribute in developing a local instruction theory for teaching and learning of integer concept and integer addition. In design research, the Hypothetical Learning Trajectory (HLT) plays important role as a design and research instrument. It was designed in the phase of preliminary design and tested to three students of grade six OASIS International School, Ankara – Turkey. The result of the experiments showed that temperature in the thermometer context could stimulate students’ informal knowledge of integer concept. Furthermore, strategies and tools used by the students in comparing and relating two temperatures were gradually be developed into a more formal mathematics. The representation of line inside thermometer which then called the number line could bring the students to the last activity levels, namely rules for adding integer, and became the model for more formal reasoning. Based on these findings, it can be concluded that students' learning integer concept and integer addition developed through RME levels.Keywords: integer concept, integer addition, Realistic Mathematics Education